Expired Medication Detection Information System Using the First Expired First Out Method: Case Study of One Pharmacy in Bandung - Nisa Nur Malasari; Jajat Sudrajat (LPPM STMIK Mardira Indonesia, 2023)
A pharmacy is a facility where diverse pharmaceutical operations occur, including acquiring, formulating, and distributing medications. The utilization of information technology has experienced a substantial rise in the current digital age, particularly in the realm of healthcare. An integrated and readily accessible information system is required to oversee diverse operations in the pharmacy, including drug procurement, stock management, prescription services, and sales. This study aims to create an information system that may enhance drug procurement efficiency and monitor drug expiration in a pharmacy located in Bandung. Anticipated enhancements are likely to optimize the pharmacy's operational efficiency. The expiration of pharmaceuticals can be attributed to several factors, such as the absence of regular drug inspections due to staffing constraints, human mistakes, excessive drug procurement, and unpredictable patient demands. In order to tackle these problems, it is necessary to implement a system that can detect expired drugs. The purpose of this system is to streamline the management of drug inventory by monitoring and tracking expired drugs. It also implements the First Expired First Out (FEFO) strategy, which prioritizes the usage of drugs with closer expiration dates over those with longer expiration dates.